Weak Constitutional Obedience Regarding the Extension of PT Freeport Indonesia's Business License with the United States in 2023 - Oktatiana, Rifka Salma (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2024)
The statement outlines the chronology and implications of PT Freeport Indonesia's business license extension in the context of the Indonesian constitution. In 2017, the government issued a Special Mining Business License (IUPK) to PT Freeport, replacing the Contract of Work, with the aim of enabling continued mining operations in Papua. However, this extension raises questions about compatibility with the constitution, particularly in terms of state sovereignty over natural resources and environmental protection. Discussions also covered the legal consequences related to divestment of shares and the timing of the license extension. The meeting between President Jokowi and Freeport's CEO was also highlighted, highlighting potential rule violations related to the license extension. This statement emphasizes the importance of considering constitutional principles, including state sovereignty, environmental protection, and community welfare, in the regulation of PT Freeport's business license extension.